Organic Ion Template‐Guided Solution Growth of Ultrathin Bismuth Oxyselenide with Tunable Electronic Properties for Optoelectronic Applications. (12th May 2022) - Dang, Le‐Yang; Liu, Mingqiang; Wang, Gui‐Gen; Zhao, Da‐Qiang; Han, Jie‐Cai; Zhu, Jia‐Qi; Liu, Zheng
Abstract: 2D Bi2 O2 Se has recently attracted widespread research interest due to its high electron mobility and good air stability with tunable bandgap. However, the direct and controllable growth of large‐size, high‐quality ultrathin Bi2 O2 Se with tunable electronic properties remains a great challenge. Here, an organic ion template‐guided solution growth method, is developed using water as a solvent to efficiently obtain high‐quality 2D Bi2 O2 Se. Significantly, the thicknesses and morphologies of 2D Bi2 O x Se with various oxygen deficiencies; are also achieved. Optical spectroscopic results indicate that oxygen defects can dramatically tune the electronic properties of Bi2 O2 Se, such as work function, band gap, and energy‐band positions. As a result, the optimized Bi2 O2 Se devices exhibit a high photoresponsivity of 842.91 A W −1, photo‐detectivity of 8.18 × 10 12 Jones under 532 nm laser, and electron mobility of 334.7 cm 2 V −1 s −1 . This work proposes a new green solution method to synthesize large‐sized, high‐quality Bi2 O2 Se with tunable electronic structures that can be extended for various applications and provides a new possibility of transfer‐free large‐scale device manufacturing. Abstract : 2D Bi2 O2 Se single crystals are synthesized efficiently by organic ion template‐guided solution method using ammonium bismuth citrate and are transformed into ultrathin nanosheets after being washed. High‐performance Bi2 O2 Se optoelectronic devices are fabricated by using transfer‐free Bi2 O2 Se nanosheets on SiO2 /Si substrate.